Evaluation of GPT-4's Chest X-Ray Impression Generation: A Reader Study on Performance and Perception - Sebastian Ziegelmayer; Alexander W Marka; Nicolas Lenhart; Nadja Nehls; Stefan Reischl; Felix Harder; Andreas Sauter; Marcus Makowski; Markus Graf; Joshua Gawlitza (JMIR Publications, 2023)
Exploring the generative capabilities of the multimodal GPT-4, our study uncovered significant differences between radiological assessments and automatic evaluation metrics for chest x-ray impression generation and revealed radiological bias.